2023
DOI: 10.1002/adfm.202303994
|View full text |Cite
|
Sign up to set email alerts
|

Robust Self‐Catalytic Reactor for CO2 Methanation Fabricated by Metal 3D Printing and Selective Electrochemical Dissolution

Abstract: The methanation of CO2 has been actively pursued as a practical approach to mitigating global climate change. However, the complexity of the catalyst development process has hindered the development of new catalysts for CO2 methanation; as a result, few catalysts are commercially available. Herein, a multifunctional self‐catalytic reactor (SCR) is prepared via metal 3D printing and selective electrochemical dissolution as a method to not only simplify the catalyst development process but also fabricate active … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Methane synthesis from CO 2 hydrogenation (CO 2 + 4H 2 / CH 4 + 2H 2 O, DH°= −165 kJ mol −1 ), known as the Sabatier reaction, is an exothermic process that is more thermodynamically favorable than many other hydrogenation routes. 21,171 However, it still suffers from signicant kinetic limitations due to the intrinsical inertness of linear CO 2 and the involvement of an eight-electron transfer process. 165,172,173 Several metal-containing catalysts have been demonstrated as effective candidates for this reaction, typically based on Ru, Rh, Pd, and Ni NPs on supported materials, with Ni-based catalysts being the most popular one because of the low cost and rich reserves.…”
Section: Co 2 Methanationmentioning
confidence: 99%
“…Methane synthesis from CO 2 hydrogenation (CO 2 + 4H 2 / CH 4 + 2H 2 O, DH°= −165 kJ mol −1 ), known as the Sabatier reaction, is an exothermic process that is more thermodynamically favorable than many other hydrogenation routes. 21,171 However, it still suffers from signicant kinetic limitations due to the intrinsical inertness of linear CO 2 and the involvement of an eight-electron transfer process. 165,172,173 Several metal-containing catalysts have been demonstrated as effective candidates for this reaction, typically based on Ru, Rh, Pd, and Ni NPs on supported materials, with Ni-based catalysts being the most popular one because of the low cost and rich reserves.…”
Section: Co 2 Methanationmentioning
confidence: 99%
“…The catalytic active sites in an SCR are generated within the reactor itself through self-oxidation or dissolution, simplifying post-treatment processes and enhancing reusability. [7,9] This integrated approach not only optimizes reactor capacity utilization but also streamlines catalyst development, potentially accelerating the development of new commercial catalysts. Wei et al utilized selective laser sintering (SLS) to fabricate an SCR with Fe, Co, and Ni for harsh catalytic reactions such as Fisher-Tropsch (FT) reactions, CO 2 hydrogenation, and methane dry reforming, demonstrating high performance and reusability (Figure 4a and b).…”
Section: Advancements In Metal 3d Printing Technology In Catalytic Fieldmentioning
confidence: 99%
“…[8] Kim et al created Ni-SCRs with four different pattern shapes using SLM for CO 2 methanation and applied electrochemical methods to expose active Ni sites (Figure 4c and d). [9] After the appropriate electrochemical treatment, the Ni-SCR was transformed into a highly active catalyst, achieving 80 % CO 2 conversion in the P4 pattern with high stability and reusability. [5] b) Repeating micromixer reactor prepared by STS 316 for benzaldehyde and furfural reduction.…”
Section: Advancements In Metal 3d Printing Technology In Catalytic Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, metal 3D-printing methods, such as selective laser melting (SLM), selective laser sintering (SLS), and direct metal printing, , have been extended into the catalysis field because they can be used to integrate a catalyst and reactor into a single system . We have demonstrated that metal 3D printing is a feasible method to prepare a multifunctional self-catalytic reactor (SCR) using Hastelloy X powder as a starting material . Selective electrochemical dissolution of the SCR successfully transformed the original inert surface, which consisted of a Cr- and Fe-based passivation layer, into a Ni-enriched surface that is active as a robust catalyst for CO 2 methanation.…”
Section: Introductionmentioning
confidence: 99%